Apolipoprotein E receptor 2 is involved in the thrombotic complications in a murine model of the antiphospholipid syndrome - Romay-Penabad, Zurina (American Society of Hematology, 2011)
Antiphospholipid (aPL)/anti-β(2) glycoprotein I (anti-β(2)GPI) antibodies stimulates tissue factor (TF) expression within vasculature and in blood cells, thereby leading to increased thrombosis. Several cellular receptors have been proposed to mediate these effects, but no convincing evidence for the involvement of a specific one has been provided. We investigated the role of Apolipoprotein E receptor 2 (ApoER2′) on the pathogenic effects of a patient-derived polyclonal aPL IgG preparation (IgG-APS), a murine anti-β(2)GPI monoclonal antibody (E7) and of a constructed dimeric β(2)GPI I (dimer), which in vitro mimics β(2)GPI-antibody immune complexes, using an animal model of thrombosis, and ApoER2-deficient (−/−) mice. In wild type mice, IgG-APS, E7 and the dimer increased thrombus formation, carotid artery TF activity as well as peritoneal macrophage TF activity/expression. Those pathogenic effects were significantly reduced in ApoER2 (−/−) mice. In addition, those effects induced by the IgG-APS, by E7 and by the dimer were inhibited by treatment of wild-type mice with soluble binding domain 1 of ApoER2 (sBD1). Altogether these data show that ApoER2 is involved in pathogenesis of antiphospholipids antibodies.